2022
DOI: 10.1039/d2ra02720h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-assisted-synthesis of isoindolin-1-one derivatives

Abstract: Functionalized isoindolin-1-ones have been prepared in short reaction time and excellent yields from 3-alkylidenephtalides and primary amines under ultrasonic irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…The one-pot synthesis of 3-substituted-isoindolin-1-ones 1 was initially investigated by performing the nucleophilic addition reaction between ( Z )-3-benzylideneisobenzofuran-1(3 H )-one 2a (prepared from 2-iodobenzoic acid and terminal alkynes via ultrasound-assisted-Sonogashira coupling 27 ) and butylamine 3a in iso-propanol at 50 °C under ultrasound irradiation. This reaction in situ produced the synthetic intermediate of 3-hydroxyisoindolin-1-ones 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-pot synthesis of 3-substituted-isoindolin-1-ones 1 was initially investigated by performing the nucleophilic addition reaction between ( Z )-3-benzylideneisobenzofuran-1(3 H )-one 2a (prepared from 2-iodobenzoic acid and terminal alkynes via ultrasound-assisted-Sonogashira coupling 27 ) and butylamine 3a in iso-propanol at 50 °C under ultrasound irradiation. This reaction in situ produced the synthetic intermediate of 3-hydroxyisoindolin-1-ones 7 .…”
Section: Resultsmentioning
confidence: 99%
“…We also found that ultrasound irradiation may accelerate the rate of those reactions. 27 Our strategy was driven to meet the green chemistry principles as an efficient approach for 3-isoindolin-1-ones 1. Based on the promising preliminary results, we envisioned that performing both reactions based on ultrasound-assisted-one-pot reaction would efficiently generate 3-isoindolin-1-ones 1.…”
Section: Introductionmentioning
confidence: 99%
“…The reason behind the enhanced conversion under ultrasonic irradiation might be the cavitation phenomenon caused by ultrasonic irradiation which may supply energy to the reaction medium by creating a repeating pattern of compressions and rarefaction. 53,54 This results in an increase in the rate of the reaction and the yield. Further, it is obvious from Table 3 that the catalyst synthesized in the presence of additives offers higher catalytic activity which might be due to the different surface properties of the particles in different samples.…”
Section: Mössbauer Spectroscopy Studymentioning
confidence: 99%
“…Finally, the pyrrolo[3,4- b ]pyridin-5-one is a fused-type bis -heterocycle that is also of high interest in medicinal chemistry. It includes the antidiabetic agent BMS-767778 ( 3 , Figure 1 ) [ 9 ] which is an N- sp 2 -containing surrogate of the naturally occurring isoindolin-1-one ( 3′ , Figure 1 ) [ 10 ]. The pyrrolo[3,4- b ]pyridin-5-one system is very special in our research group.…”
Section: Introductionmentioning
confidence: 99%